2002
DOI: 10.1590/s0066-782x2002001400006
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and peripartum cardiomyopathy: a comparative and prospective study

Abstract: Objective -To assess pregnancy outcome in women with peripartum cardiomyopathy and to compare it with idiopathic cardiomyopathy. Peripartum cardiomyopathy is a rare disease of unknown cause that affects women of reproductive age. Its incidence is related to the peripartum period. Hypotheses of its cause are focused on the physiologic relationship between pregnancy and the postpartum period and infective genetic disorders and hormonal and metabolic changes [1][2][3] . The criteria for diagnosis of peripartum ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The natural history of peripartum cardiomyopathy was described in cohort studies that followed up patients with clear signs and symptoms of this condition [1,[9][10][11][12][19][20][21][22][23]. However, the occurrence of asymptomatic ventricular dysfunction associated with puerperium remains relatively understudied.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of peripartum cardiomyopathy was described in cohort studies that followed up patients with clear signs and symptoms of this condition [1,[9][10][11][12][19][20][21][22][23]. However, the occurrence of asymptomatic ventricular dysfunction associated with puerperium remains relatively understudied.…”
Section: Discussionmentioning
confidence: 99%
“…None of the dilated cardiomyopathy patients had a significant decline in cardiac status. In contrast, a study of 26 women from Brazil suggested that cardiac complications were higher in the idiopathic cardiomyopathy cohort when compared with those with persistent left ventricular dysfunction due to peripartum cardiomyopathy (45). A study from Haiti identified 99 women with peripartum cardiomyopathy, 15 of whom had subsequent pregnancies.…”
Section: Dilated Cardiomyopathymentioning
confidence: 98%
“…Currently, there is no consensus regarding recommendations for future pregnancy after PPCM, but left ventricular function is considered the most important prognostic factor and must be the most parameter when counseling patients with PPCM about a new pregnancy [144].…”
Section: Pregnancy Outcome In Women With Ppcmmentioning
confidence: 99%